Potential for Public-Private Partnership in East Timor - Guasch, Jose Luis; Cuttaree, Vickram (World Bank, Washington, DC, 2013)
This note has been prepared in the context of the International Investment Conference on "Investment and National Building in Timor Leste" that took place on 21-22 October, 2010 in Dili, Timor-Leste. One of the topics of the international conference was a discussion of the potential for Public-Private Partnership in East Timor. This note elaborates on the key messages of the presenters during the conference and it is hoped that it will help guide the Government in moving forward with its PPP agenda.